Penggunaan Stiker Whatsapp Dan Pengaruh Terhadap Efektivitas Komunikasi Digital Dikalangan Orang Tua (Studi Kasus Pada Orang Tua Di Baladewa Rt 08 Kota Bandung) - Sukmawati, Nisrina; Hidayat, Dasrun (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The advent of instant messaging apps like WhatsApp has changed the way parents communicate digitally. One of the more popular features is the use of stickers in messages. This study aims to determine the use of WhatsApp stickers in digital communication among parents in Baladewa Rt 08, Bandung city, and measure its impact on the effectiveness of their communication. This research uses quantitative methods, the data collection technique is in the form of a questionnaire to a group of parents who actively use WhatsApp stickers in daily communication. The results showed that the use of WhatsApp stickers can increase emotional expression and creativity in parents' digital communication and how the use of these stickers affects their communication effectiveness in facing the challenges of modern digital communication. However, there is also the constraint that the use of WhatsApp stickers may compromise communication effectiveness in some contexts. Therefore, this study provides an in-depth insight into how the use of WhatsApp stickers affects digital communication among parents, with diverse impacts for the development of communication and interaction technologies. The conclusions of this study can help in developing an understanding of how parents interact with digital communication technologies.